Will US inflation awake from the dead? The role of slack and non-linearities in the Phillips curve - Bruno Albuquerque; Ursel Baumann (European Central Bank (ECB), 2017)
The response of US inflation to the high levels of spare capacity during the Great Recession of 2007-09 was rather muted. At the same time, it has been argued that the short-term unemployment gap has a more prominent role in determining inflation, and either the closing of this gap or non-linearities in the Phillips curve could lead to a sudden pick-up in inflation. We revisit these issues by estimating Phillips curves over 1992Q1 to 2015Q1. Our main findings suggest that a Phillips curve model that takes into account inflation persistence, inflation expectations, supply shocks and labour market slack as determinants explains rather well the behaviour of inflation after the Great Recession, with little evidence of a "missing deflation puzzle". More important than the choice of the slack measure is the consideration of time-variation in the slope. In fact, we find that Phillips curve models with time-varying slope coefficients are able to outperform significantly the constant-slope model as well as other non-linear models over 2008Q1-2015Q1.
Keywords: E31; E37; E58; 330; inflation dynamics; labour market slack; Phillips curve